Safety of convalescent plasma to treat COVID-19: Systematic review - Ephrem Awulachew; Kuma Diriba; Asrat Anja; Firehiwot Belayneh (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
Background: Currently, Coronavirus disease (COVID-19) was reported in more than 204 countries. As of April 10, 2020, a total of 1,605,729 confirmed cases and 95,766 deaths had been reported worldwide. There are no approved specific antiviral agents targeting the novel virus. Convalescent plasma transfusion might be effective against the infection. Food and Drug Administration (FDA) has also approved the emergency use of investigational COVID-19 convalescent plasma to treat severely ill COVID-19 patients.  Objective: The aim of this study was to systematically review disease outcome and safety of convalescent plasma to treat COVID-19.  Method: We searched literature published in English from December 20 /2019 to April 10/2020 on electronic databases. Using R software we have conducted a systematic analysis, frequency, mean, standard deviation, and chi-square test.  Result: The average age of the participants in the included was 55.7 with a standard deviation of 13.9. The average days of recovery or test negative for the COVID-19 PCR test after convalescent plasma therapy were 9.6 days (95% CI 2- 30 days). About 43% (9/21) had a history of comorbidity.  The average date of recovery of patients with co-existing chronic diseases infected by COVID-19 after convalescent plasma therapy was about 12 days relatively prolonged than patients without the co-existing disease (7.6 days). No series adverse effects have been demonstrated in patients who have received convalescent plasma transfusion.  Conclusions: This study indicated that convalescent plasma transfusion might be a potential treatment for critically ill patients with COVID-19 pneumonia. It could be helpful to reduce the risk of mortality of critically ill patients. We demonstrated no serious adverse reactions associated with the transfusion of convalescent plasma.